Advanced nitrogen removal from municipal wastewater via two-stage partial nitrification-simultaneous anammox and denitrification (PN-SAD) process. (May 2020) - Deng, Shiyun; Peng, Yongzhen; Zhang, Liang; Wu, Lei
Graphical abstract: Highlights: NAR was stabilized at above 95% by low DO combine with aeration time control. Synergistic nitrogen removal achieved by introducing municipal wastewater. Partial denitrification was another way to supply nitrite in the SAD system. The TIN removal efficiency reached 97.1% with a short HRT of 6 h. Abstract: A modified two-stage anammox process was constructed and achieved advanced nitrogen removal from municipal wastewater. The first stage was Partial Nitrification (PN), in which nitrite accumulation rate was over 95% by controlling dissolved oxygen concentration (<1 mg/L) and aeration time (90–120 min). The second stage was simultaneous anammox and denitrification (SAD), in which the reactor was fed with the effluent of the first stage and a part of raw wastewater. The effluent total inorganic nitrogen (NH4 + -N, NO2 − -N and NO3 − -N) was only 1.6 ± 0.8 mg N/L and the nitrogen removal efficiency reached 97.1%. The proportion of anammox in nitrogen removal was up to 73–82% and Candidatus Brocadia was the main anammox genus accounted for 8.0–2.2%. And partial denitrification occurred with the appearance of Thauera (0–1.0%). The PN-SAD process is an energy-saving treatment for municipal wastewater with a total hydraulic retention time of 6 h.